Diagnostic Challenges and Management of Kikuchi-Fujimoto Disease: A Rare Case Report - Zukhruf fatima (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Kikuchi-Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a rare, benign, and self-limiting condition primarily affecting young Asian females. It is characterized by fever, lymphadenopathy, and systemic symptoms, and is frequently misdiagnosed due to clinical similarity to infectious, autoimmune, or malignant disorders. Although its aetiology remains uncertain, viral and autoimmune triggers have been proposed. Diagnosis relies on histopathological evaluation of lymph node tissue. Methods: A retrospective analysis was conducted using the patient’s clinical history, laboratory findings, and imaging results. The diagnosis was confirmed through histopathological examination following excisional lymph node biopsy. Written informed consent for publication was obtained from the patient. Ethical approval was not required, as per the institutional policy regarding case reports. Case Presentation: A 42-year-old male with type 2 diabetes mellitus, residing in Karachi, Pakistan, presented with an 18-month history of recurrent high-grade fever, unintentional weight loss, and a progressively enlarging occipital lymph node. Multiple hospital admissions and empirical antibiotic therapies failed to achieve symptom resolution. On physical examination, the occipital lymph node was firm, mobile, and non-tender. Laboratory workup revealed mild normocytic anemia, leukopenia, and elevated inflammatory markers. Radiological imaging and autoimmune serologies were unremarkable. Excisional biopsy of the lymph node demonstrated necrotizing lymphadenitis with karyorrhectic debris and absence of neutrophilic infiltration, consistent with Kikuchi-Fujimoto disease. Significant clinical improvement was observed following initiation of corticosteroid therapy. Conclusion: This case underscores the diagnostic challenge posed by KFD, particularly in older male patients presenting with prolonged fever and lymphadenopathy—an atypical demographic. The condition may closely mimic tuberculosis or lymphoma, potentially leading to misdiagnosis and inappropriate management. Histopathological confirmation through excisional biopsy remains essential for diagnosis. Early recognition and corticosteroid therapy can result in favorable clinical outcomes. Keywords: Kikuchi-Fujimoto disease, necrotizing lymphadenitis, fever of unknown origin, corticosteroid therapy, lymphadenopathy